Short‐term multimodal prehabilitation improves functional capacity for colorectal cancer patients prior to surgery. Issue 2 (14th April 2021) - Suen, Michael; Liew, Andre; Turner, Jane D.; Khatri, Sonia; Lin, Yanlan; Raso, Kristy L.; Vardy, Janette L.
Abstract: Aim: Evaluate feasibility and outcomes of a multimodal prehabiliation program in patients with stage I‐III colorectal cancer (CRC) awaiting surgery. Methods: Patients scheduled for elective CRC resection at Concord Repatriation General Hospital were recruited from pre‐admission clinic between January and November 2018. Participants received a 2‐4 week prehabilitation program consisting of supervised exercise sessions, nurse‐led phone support, and written nutritional information. Participants were assessed at baseline, pre‐surgery, and 4 weeks post‐surgery. Results: Twenty‐two patients participated in the program: 55% male; median age 73 (56‐86) years. Six (28%) required an interpreter. At baseline, 19 of 22 (86%) had at least one comorbidity. Median intervention length was 11.5 days (range 7‐29). Participants attended 79% of scheduled exercise sessions (range 33‐100%, mean 3.5 sessions) and 66% of nurse support calls (range 0‐100%, mean 2.6 sessions). Between baseline and pre‐surgery, participants reported increasing mean unsupervised moderate‐intensity aerobic exercise from 17 (range 0‐210) to 73 minutes/week (range 0–276) and mean vigorous‐intensity aerobic exercise from 0 to 24 minutes/week (range 0‐300). Resistance exercise sessions increased from 0.6 to 2.6 times/week. Mean 6‐minute walk test distance increased by 48 meters (435‐483 m) and 30‐second "sit to stand" by 1.6 repetitions. Small improvements were seen in global quality of life and fatigue. Nutritional status and body composition remained unchanged. All participants were satisfied/strongly satisfied with the program and would recommend it to others. Conclusion: Our multimodal prehabilitation program was feasible in CRC patients inclusive of those from non‐English speaking backgrounds, with improvement in functional capacity before CRC surgery. Abstract : Multimodal prehabilitation programs are feasible for patients prior to resection for early‐stage colorectal cancer. Our exercise, nutrition, and nurse‐led phone support program showed improvement in aerobic and resistance exercise, distance walked in 6‐minutes and small improvements in global quality of life and fatigue.